Treatment of COVID‐19 patients with the anti‐CD6 antibody itolizumab - Caballero, Armando (Clin Transl Immunology, 2020)
OBJECTIVES: COVID‐19 can lead to a hyperinflammatory state. CD6 is a glycoprotein expressed on mature T lymphocytes which is a crucial regulator of the T‐cell activation. Itolizumab is a humanised antibody targeting CD6. Nonclinical and clinical data in autoimmune diseases indicate that it lowers multiple cytokines primarily involving the Th1/Th17 pathway. The primary objective of this study was to assess the impact of itolizumab in arresting the lung function deterioration of COVID‐19 patients. Secondary objectives included safety, duration of ventilation, 14‐day mortality and evaluation of interleukin 6 concentration. METHODS: Patients with confirmed SARS‐CoV‐2 received itolizumab in combination with other therapies included in the national protocol for COVID‐19. RESULTS: Seventy critical, severe or moderate patients were treated with itolizumab in 10 Cuban hospitals. Median age was 68, and 94% had comorbidities. After 72 h, most patients improved the PO(2)/FiO(2) ratio and reduced FiO2 requirements. Ventilation time was 8 days for critical and 1 day for severe cases. Ten patients had related adverse events while 3 subjects developed related serious events. In 30 patients, interleukin 6 decreased in individuals with high level and did not change in those with lower concentration. Fourteen‐day lethality rate was 4% and 18% for moderate and severe patients, respectively. The proportion of moderate or severe patients with ventilation or death at day 14 was 9.8%. Time to treatment, neurological manifestations and biomarkers such as NLR were significantly associated with higher lethality. CONCLUSIONS: The opportune administration of itolizumab might interrupt the hyperinflammatory cascade and prevent COVID‐19 morbidity and mortality.